Significance of Balanites aegyptiaca (L.) as Molluscicide against Bulinus wrighti (Mandahl, 1965) snails: A review of concepts - Yalli Abu Abdulkarim (BIORE Scientia Academy, 2023)
The objective of this paper is to bring a conceptual review of schistosomiasis and application of Balanites aegyptiaca in controlling the host (Bulinus wrighti) of the disease. The snail host (Bulinus wrighti) serve as the host that transmits schistosomiasis disease to humans; therefore, for effective management it shall be controlled. Whereas, schistosomiasis is mostly due to the parasites, S. haematobium, S.japonicum, S. mekongi, and S. intercalatum. Those parasites deposit their eggs in freshwater environment that tend to further develop in snail. Snail shed numerous cercariae that under opportunity invade the human body (for example, farmers, fishers, swimmers, etc). In the human body, the schistosomule is made from the cercariae; thereof allowed to be transported to various body parts (such as liver, messentric veins) depending on the specific parasite involved. Thereafter, eggs are formed and definitive host reactions are elicited in form of clinical portends (such as cough, fever, abdominal pain, fatigue, skin symptoms) in respective of the parasite species. In Africa, millions of individuals are infected, and millions are at risk. To prevent the disease, natural or synthetic mollusucicides could be applied to kill the snail. Natural products such as Balanites aegyptiaca are proven with good virtues to act as mollusucicides. B. aegyptiaca in its various parts contain active compounds such as saponins, tannins, alkaloids, terpenoids, flavonoids, etc that might be responsible for the activities of the plant. Therefore, it is relevant to advocate for natural-bases products such as B.aegyptiaca for prevention of schistosomiasis due to accessibility, cheapness, effectiveness, poverty, and culture-based traditions.